2014
DOI: 10.1111/1469-0691.12621
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of traveller’s diarrhoea: evaluation of a multiplex PCR tool to detect different enteropathogens

Abstract: Traveller's diarrhoea (TD) is the most common illness reported in international travellers. TD is caused by a wide range of pathogens, including bacteria, viruses and parasites. Multiplex PCR assays can be especially useful for studying the aetiology of TD. The first objective of this study was to evaluate the utility of the commercially available multiplex PCR (xTAG(®) Gastrointestinal Pathogen Panel (GPP)) for the diagnosis of TD. A total of 185 stool specimens obtained from 174 patients were processed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 25 publications
(47 reference statements)
6
54
2
Order By: Relevance
“…11,12,[20][21][22][23]25,[29][30][31][32][33][34]38,39 However, only four studies reported outcomes of verification by pathogen. 20,23,25,30 Study design Table 7 characterises the design heterogeneity among the studies reported, which should be noted when considering the pooled study outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11,12,[20][21][22][23]25,[29][30][31][32][33][34]38,39 However, only four studies reported outcomes of verification by pathogen. 20,23,25,30 Study design Table 7 characterises the design heterogeneity among the studies reported, which should be noted when considering the pooled study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study 11 differentiated between hospital-based samples (from children admitted with suspected viral gastroenteritis and children presenting to the emergency room) and community-based samples [adult and child travellers whose samples were submitted by general practitioners (GPs)]; the study population consisted of children and travellers only. Seven studies 19,22,26,27,29,35,39 reported the setting sufficiently to allow judgement on the origin of the infection (hospital vs. community). The majority of studies 11,12,20,21,[23][24][25]28,[30][31][32][33][34][36][37][38] reported recruitment of hospitalised patients, for which a mixed population should be assumed (in terms of origin of infection) as it is unclear at what point in time during hospitalisation each infection occurred.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations